Group Learning With Wikipedia: A Structured Approach - Robert Lieberthal; Jacquelyn McRae; Juan Leon (Association of American Medical Colleges, 2016)
Abstract Introduction Previous studies have shown that group learning may help students retain a greater amount of information than tradition teacher-student model. For online courses that lack direct interpersonal contact, incorporating group learning into online learning can be more challenging than the traditional in-person courses. This resource consists of a structured multiple mini-team assignments. The idea of incorporating Wikipedia into the assignment was premised on the principle that students are more apt to gain a greater depth of knowledge when motivated by teaching others. Methods This activity is designed to be completed over a sequence of 8 weeks. The activity has historically complemented an online course; therefore, students complete components of the assignment in an unstructured time. Each component of the activity is designed to be completed in 3-5 hours. Students are required to have some baseline knowledge of the subject before beginning the project. Students also should be knowledgeable of proper sources of peer-reviewed information. Results This activity has been implemented a total of seven times in an online, 8-week format for the past 4 years. During that time, students have developed full-text reviews on a variety of health economics topics. Seventy percent of the students have voluntarily submitted their assignments to Wikipedia to add to a public repository. Discussion To our knowledge this is the first MedEdPORTAL resource that gives a structured approach to the development of a Wikipedia article. The peer review process is a unique feature of the workshop version of this activity, which has not been synthesized in practice.